Government cloud computing and the policies of data sovereignty - Kristina Irion (International Telecommunications Society (ITS), 2011)
Government cloud services are a new development at the intersection of electronic government and cloud computing which holds the promise of rendering government service delivery more effective and efficient. Cloud services are virtual, dynamic and potentially stateless which has triggered governments' concern about data sovereignty. This paper explores data sovereignty in relation to government cloud services and how national strategies and international policy evolve. It concludes that for countries data sovereignty presents a legal risk which can not be adequately addressed with technology or through contractual arrangements alone. Governments therefore adopt strategies to retain exclusive jurisdiction over government information.
Keywords: H11; H73; H83; 330; cloud computing; electronic government; data sovereignty; data ownership; information assurance; international data transfers